2022
DOI: 10.1111/ced.15109
|View full text |Cite
|
Sign up to set email alerts
|

Tinea auricularis: a neglected tinea incognito

Abstract: Ultraviolet dermoscopy is a rapid and noninvasive diagnosis tool for tinea auricularis caused by Microsporum canis, which facilitated early treatment with systemic antifungals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Zhi et al reported a case of child with unidentifiable ear auricularis, which manifested as persistent erythematous papules and pruritus in the left ear. 4 Hamzelou et al reported an 80-year-old man with fungal infection on the ear who presented with the clinical manifestations of erythema, scales and pustules. Tinea auricularis is uncommon and easily misdiagnosed; however, the notable observation is the sole involvement of the ear.…”
Section: Discussionmentioning
confidence: 99%
“…Zhi et al reported a case of child with unidentifiable ear auricularis, which manifested as persistent erythematous papules and pruritus in the left ear. 4 Hamzelou et al reported an 80-year-old man with fungal infection on the ear who presented with the clinical manifestations of erythema, scales and pustules. Tinea auricularis is uncommon and easily misdiagnosed; however, the notable observation is the sole involvement of the ear.…”
Section: Discussionmentioning
confidence: 99%
“…The microorganism is associated with endothrix infection of the hair shaft, including vellus hair. UVFD reportedly shows bright white coiled and curly vellus hair [ 18 , 48 50 ]. These observations may facilitate monitoring therapeutic response and follow-up [ 50 ].…”
Section: Methodsmentioning
confidence: 99%